Reinstatement and Lectotypification of Memecylon deccanense (Melastomataceae): An Endemic Species of the Western Ghats, India. - Kumar, Santhosh; Vikraman, R Raj; S, Shailajakumari; Kumar, P K Suresh; Sreelekshmy, R S (Journal of Tropical Life Science, 2020)
As part of the ex-situ conservation of the wild ornamental plants at JNTBGRI, several species of Memecylon were collected and introduced from the Western Ghats. While working on the taxonomy of the collected plants, it was found that a well defined species Memecylon deccanense C.B.Clarke Â has been reduced recently to the synonym of M.heyneanum Benth. ex Wight & Arn. A detailed study by relevant literature, live and herbarium specimens, and type specimens housed at different herbaria, it is reinstated as a distinct species and a lectotype is designated here. Relevant photographs and images of type specimens of M.deccanense and M.heyneanum also provided to facilitate its easy identification.